2004
DOI: 10.2134/jeq2004.1183
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization from Surface‐Applied Poultry Litter under Conservation Tillage Management Practices

Abstract: Land application of poultry litter can provide essential plant nutrients for crop production, but ammonia (NH(3)) volatilization from the litter can be detrimental to the environment. A multiseason study was conducted to quantify NH(3) volatilization rates from surface-applied poultry litter under no-till and paraplowed conservation tillage managements. Litter was applied to supply 90 to 140 kg N ha(-1). Evaluation of NH(3) volatilization was determined using gas concentrations and the flux-gradient gas transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 27 publications
(38 reference statements)
4
63
0
2
Order By: Relevance
“…This provides a strong impetus for efforts in both energy production and waste reduction. For example, more than 12 million dry tonnes of litter is generated every year from the U.S. poultry industry [6], and proper disposal of this waste presents a major challenge. Pyrolysis of poultry litter to produce bioenergy and biochar has been suggested as a potential solution to this challenge [7].…”
Section: Introductionmentioning
confidence: 99%
“…This provides a strong impetus for efforts in both energy production and waste reduction. For example, more than 12 million dry tonnes of litter is generated every year from the U.S. poultry industry [6], and proper disposal of this waste presents a major challenge. Pyrolysis of poultry litter to produce bioenergy and biochar has been suggested as a potential solution to this challenge [7].…”
Section: Introductionmentioning
confidence: 99%
“…The peak of ammonia volatilization from the soil treated with conventional urea alone occurred a week later than what has normally been observed (Sangoi et al, 2003;Sharpe et al, 2004;Tasca et al, 2011;Oliveira et al, 2014). The delay in this peak in our study is probably due to the low temperatures during the experimental period, a mean of 15 °C (Figure 1), and this may have negatively affected urease activity and urea hydrolysis (Clay et al, 1990).…”
Section: Peak Of Volatilizationmentioning
confidence: 39%
“…Sharpe et al (2004) measured ammonia volatilization after addition of poultry litter to the soil and found losses up to 3.3 and 24 % of the total N applied in the winter and summer, respectively, where the highest values occurred in periods of high temperatures, drought, and high wind. Following urea application, ammonia volatilization may range from negligible values (Viero et al, 2014) up to more than 40 % of the total N applied (Oliveira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these NH 3 emissions are also a significant environmental concern because they contribute to acid rain (Sharpe et al 2004), soil acidification (van Breemen et al 1982), and N enrichment of surface waters (Hutchinson and Viets 1969;Schroder 1985;Fisher and Oppenheimer 1991). Ammonia is a chemically active gas that readily combines with nitrates and sulfates in the atmosphere to form fine particulate matter, which has been implicated in human respiratory problems and led to revised air quality standards in the United States (Dell et al 2012;Sommer and Hutchings 2001).…”
mentioning
confidence: 99%
“…Unfortunately, existing farm equipment can only apply poultry litter in conservation tillage and no-till systems by broadcasting it on the soil surface. This method leaves the litter exposed to the atmosphere, allowing substantial NH 3 volatilization (Brady 1990;Chapman and Snyder 1992;Nathan and Malzer 1994;Sharpe et al 2004), as well as nutrient losses in runoff (Edwards and Daniel 1993;Pote et al 2003). Research has shown that N losses through NH 3 volatilization from surface-applied poultry litter can reach as high as 60% of total N applied, depending on litter characteristics and environmental factors (Brinson et al 1994;Cabrera et al 1993;Cabrera and Chiang 1994;Marshall et al 1998).…”
mentioning
confidence: 99%